Comparative Evaluation of Soft Tissue Profile Changes with Herbst and Twin Block Appliances in Class II Malocclusion Patients: A Perception Study - Annapurna Kannan; Sridevi Padmanabhan (Galenos Yayinevi, 2022)
Objective: To comparatively evaluate the perception of patients' soft tissue profiles treated with Herbst and Twin Block appliances and correlate the perception with cephalometric parameters.Methods: The record of 30 patients (15 Herbst and 15 Twin Block) treated for a period of 6 months (±1.1 months) was included in the study. A total of 60 resulting profile silhouettes (from pre- and post-functional profile photographs) were evaluated by 30 examiners and were divided into 3 groups: orthodontists, general dentists, and laypersons. The profiles were arranged in a randomized order, and the examiners rated the profiles using a visual analog scale. Paired t-test and independent t-test were performed to find a significant difference within and between the appliances, respectively. A treatment outcome correlation was done using Pearson's correlation test between the visual analog scale scores and cephalometric parameters.Results: Within the appliances, the orthodontist perceived a difference with only the Twin Block appliance (P = .02). The general dentists perceived a significant difference with both Herbst (P = .02) and Twin Block (P = .001) appliances, whereas the laypersons did not perceive any profile improvement on treatment with functional appliances. However, between the appliances, no statistically significant profile difference was seen with all 3 groups of examiners. The ANB angle had a significant negative correlation (P = .007) to the visual analog scale scores given by the orthodontists for the Herbst appliance.Conclusion: No perceptible difference was found in the profile enhancement between Herbst and Twin Block appliances with all 3 groups of examiners. The ANB angle contributed to the difference in profile perception between the appliances for the orthodontists.